Diagnosis of subclinical endometritis and subsequent reproductive status in postpartum cattle - Mohammed, Salah Noori (2018)
Endometritis is one of the most common diseases that affect reproductive performance in dairy and beef cows (Sheldon et al., 2006). There is lack of studies about occurrence of subclinical endometritis and its diagnosis using cytological methods in Malaysia. Moreover, failure of response to antibiotics by pathogenic bacteria in uterine infections possibly due to drug resistance warranted the need to conduct this study. The aims of this study were: 1) to evaluate three different methods of collection of endometrial cytological samples, 2) to determine the agreement among bacteriological findings, vaginal discharges, and endometrial cytology for endometritis detection in postpartum beef cows, 3) to determine the occurrence of subclinical endometritis (SCE) in postpartum beef cows, to compare the ovarian activity between SCE and healthy cows , 4) to assess the interaction between SCE cows and selected cytokines, acute phase proteins (APPs) and 5) to evaluate the agreement between endometrial cytology and ultrasound examination for diagnosis of SCE in postpartum beef cows. All parametric data after testing by the Shapiro– Wilk test were analyzed using t-test, one-way ANOVA as well as Tukey and Duncan post hoc tests at a probability threshold, P < 0.05. For non-parametric data, Kruskal- Wallis and Mann-Whitney tests were performed; all by using SPSS software. Three different methods to collect cytological endometrial samples cotton swab (CS), cytobrush (CB) and low volume flush (LVF) were used to determine the mean of polymorphonuclear leukocytes (PMN) under high power field (HPF) microscopy (400x). Forty beef cows aged 3 to 7 years were subjected for cytological sampling at week three and four postpartum using the above methods. The mean number of PMN from CB alone was significantly higher (11.3 ± 0.53 cells HPF-1) than CS (7 ± 0.37 cells HPF-1) and LVF (6 ± 0.35 cells HPF-1) methods. Smears from CB had more endometrial cells and PMN (58.55 ± 1.41 cells HPF-1), which were significantly higher (P > 0.05) than CS and LVF methods. Both CB and CS methods yielded significantly more intact PMN and endometrial cells (62.4 % and 61.9 %) than LVF (52.4 %). In conclusion, CB was found to be better and effective technique compared with the other cytological methods. For objective 2, a total of 82 postpartum beef cows at 20–30 days post-calving, were used in this study. All the cows were examined by transrectal palpation and vaginal secretions collection. Endometrial swab samples for cytology and bacteriology were collected using CB. A four-grade system (0 = clear mucus, 1 = mucus containing flecks of pus, 2 = discharge including < 50% pus, and 3 = involving > 50% pus) was used to categorize vaginal secretions of these cows. Of the total 82 cows studied, 11% (9/82) had grade 1-3 vaginal secretions and indicated to have clinical endometritis (CE), whereas nine of the 73 clinically healthy cows (12.32%) were diagnosed with subclinical endometritis (SCE ≥ 8 % PMN). Escherichia coli was the most common bacteria isolated from SCE (42%), and CE cows (38%), which were significantly higher (P> 0.05) than healthy cows (14.6%). The antimicrobial sensitivity test assessed based on the inhibition effects on in vitro bacterial growth showed that most of the isolated bacteria were sensitive to enrofloxacin and tetracycline. To compare ovarian activity between cows with SCE and healthy cows, and also to determine the interaction between SCE and selected proinflammatory cytokines (IL- 6 and IL-8), and acute phase proteins (APPs) like haptoglobin (Hp). A total of 96 postpartum beef and 52 Friesian Sahiwal dairy cows were used. All postpartum cows were checked by transrectal palpation weekly beginning from week 3 until week 16 to evaluate uterine involution, and resumption of ovarian activity by detecting growing follicles on both ovaries. Endometrial samples were collected using CB technique between day 22 and day 28 after calving to identify cows with SCE. The occurrence of SCE was higher 15.3% (8/52) in a dairy group than the beef group 12.5% (12/96) at week 4 postpartum. Twelve beef and 8 dairy healthy cows were randomly selected as control to compare with cows diagnosed with SCE. Blood samples were collected from SCE and healthy cows from week 3 until week 7 to check the level of serum progesterone, IL-6, IL-8 and Hp. Results showed prolonged postpartum anestrus in postpartum beef cows mainly associated with cessation of ovarian activity, leading to increased days open. Progesterone concentration was less than 1 ng/mL in both SCE and healthy beef cows. In dairy cows, the resumption of ovarian activity was faster in healthy cows (20.5 ± 0.9 days) than SCE (37.1 ± 0.7 days) postpartum and the interval from calving to first ovulation was significantly shorter in healthy cows (29.4 ± 0.7 days) than cows with SCE (47.5 ± 0.9 days). Results revealed elevated levels of proinflammatory cytokines (IL-6 and IL-8) in cows with SCE (P < 0.05) compared with healthy cows during week 4 -7 postpartum in both beef and dairy groups. The level of Hp in beef and dairy group was higher (P < 0.05) in cows with SCE than healthy cows during most of the weeks of 4 -7 postpartum periods. Lastly, using ultrasonography as a diagnostic tool to diagnosis endometritis compared with endometrial cytology method was evaluated in 53 postpartum beef cows. The study was conducted between day 20 and day 35 postpartum (at week 4 and 5) postpartum using ultrasound and CB endometrial examination methods to diagnose endometritis. Results showed that the ultrasound method is a useful and practical tool to diagnose endometritis, especially when it is combined with evaluation of intrauterine fluid accumulation and the cervical diameter (≥ 5 cm). Overall, the study revealed that prevalence of SCE in cows was low and cytobrush method was found to be superior and effective technique to obtain endometrial cytological samples. E. coli was the major risk factor found associated with SCE in beef cows. The antimicrobial sensitivity test showed that most of the bacteria isolated were sensitive to enrofloxacin and tetracycline. The levels of IL-6, IL-8, Hp can use as diagnostic markers for SCE as long as these cows are without clinical diseases and not exposed to stress factors. The ovarian activity was faster significantly in healthy dairy cows than endometritis cows. Prolonged postpartum anestrus was the common cause to increased calving-to-conception interval and impaired beef reproductive performance.